AB0781 Clinical periodontal disease predicts the future development of chronic inflammatory arthritis. (23rd January 2014) - Hashimoto, M.; Yamazaki, T.; Hamaguchi, M.; Morimoto, T.; Yamori, M.; Asai, K.; Isobe, Y.; Mori, M.; Matsuo, T.; Furu, M.; Ito, H.; Fujii, T.; et al.
Abstract : Background: Recent reports suggest the correlation between rheumatoid arthritis (RA) and periodontal disease (PD). However, it is not clear whether PD affects the disease activity of arthritis or the future introduction of methotrexate (MTX) treatment in non-treated, undifferentiated arthritis patients. Objectives: To study whether PD affects arthritis activity and introduction of MTX treatment in non-treated, undifferentiated arthritis patients. We also investigated the relationship between a representative periodontal bacteria, Porphyromonas gingivalis (Pg), and arthritis activity or anti-citrullinated protein (CCP) antibody. Methods: We conducted a prospective cohort study in Kyoto University Hospital, Japan. We consequently enrolled patients who first visited the Rheumatic Disease Center without prior use of anti-rheumatic drugs or corticosteroids from May in 2011 to October in 2012. Arthritis disease activity (SDAI etc.) as well as anti-CCP antibody was systemically investigated by rheumatologists. Clinical parameters of PD (pocket depth, etc.) and subgingival plaque samples were collected by dentists and Pg genomic DNA was determined by Taqman q-PCR. Clinical PD was defined as maximal pocket depth more than 4 mm. We followed up all patients until January 2013. Results: We enrolled 103 patients, and 11 patients with osteoarthritis 4 patients with remaining teeth less than 10 teeth were excluded from the analysis. PD was associated with higher arthritis disease activity (SDAI 12.9±1.3 in PD group vs 7.3±1.3 in non-PD group, p=0.017), even adjusted for age, sex, smoking, or tooth brushing habit (effect size 0.11, p=0.004). Presence of PD in the first visit was a risk factor for the introduction of MTX treatment in the clinical course (Log-rank p=0.013, Hazard risk 2.77 (95%CI 1.23-6.25)). Although the amount of Pg was associated with pocket depth, it did not correlate with SDAI (10.7±1.6 in PD group vs 10.7±1.3 in non-PD group) or introduction of MTX treatment (Log-rank p=0.72). Either clinical PD or Pg did not correlate with anti-CCP antibody titers in this cohort. Conclusions: Clinical PD, but not the presence of Pg, was significantly associated with arthritis activity and predicts the future development of chronic inflammatory arthritis that requires MTX. Disclosure of Interest: None Declared